GREEN ECONOMY: THEORETICAL FOUNDATIONS AND STRATEGIC PROSPECTS OF SUSTAINABLE DEVELOPMENT - Ulug’murodov Farhod Faxriddinovich; Toshboyeva Sabrina (TADQIQOTLAR, 2026)
ABSTRACT This article is aimed at analyzing the theoretical foundations of the green economy concept, systematically examining its ecological, economic, and social dimensions, and evaluating its impact on sustainable development strategies. The study employs qualitative methodology, integrating policy documents from international organizations, case study analysis, and multi-dimensional assessment methods. Primary sources selected include reports from the United Nations Environment Programme (UNEP), the World Bank, the International Labour Organization (ILO), and current academic literature. The research results demonstrate that the transition to a green economy has the potential to create up to 24 million new jobs in the renewable energy sector and could add trillions of dollars in additional value to the global economy by 2050. However, this transition requires substantial initial investments, institutional restructuring, and social adaptation mechanisms. Key challenges identified in the article include financial barriers, policy inconsistencies, and industrial sector resistance to structural change. Proposed solutions include carbon pricing mechanisms, international financial cooperation, and just transition strategies.